Assessment of Iron Ore Ex-Mining Lake: Seasonal Influence on Water Quality of Tasik Puteri, Bukit Besi, Malaysia - Ambong Khalid, Sopiah; Fauziah Syed Draman, Sarifah; Rozaimah Sheikh Abdullah, Siti; Anuar, Nornizar (International Journal of Engineering and Technology, 2018)
Tasik Puteri, Bukit Besi has been chosen to be monitored its water quality seasonally since it is known as the main water source for iron ore washing process a decade ago. In this study, water samples from 14 sampling station were analyzed for dissolved oxygen, pH, electrical conductivity (EC) and temperature in three different seasons, which covered the normal season (August 2016), wet season (November 2017) and dry season (Jan 2018). This study revealed that the lake is acidic with pH range from 2.96 â€“ 4.32 in normal season, 2.80 â€“ 4.40 in the wet season and 2.85 â€“ 3.88 in dry season clearly fall in Class V of the Interim National Water Quality Standard (INWQS), which is highly polluted water where none of the uses of the other classes can be applied to the water. TheÂ mean temperature for the three months was within the normal range which is Class I, electrical conductivity are categorized under class I while dissolved oxygen in Class I for normal season, Class IIA/IIB for wet season and Class I for dry season. Statistical analysis of one way ANOVA test indicates that all measured parameters are shown significant difference by the seasonal changes. In summary, the water quality of Tasik Puteri, Bukit Besi should be extensively monitored since deterioration of water quality was clearly observed in terms of pH.Â Â Â